Efficacy and safety of dapagliflozin in addition to insulin therapy in Japanese patients with type 2 diabetes: Results of the interim analysis of 16‐week double‐blind treatment period. Issue 4 (22nd January 2016) - Araki, Eiichi; Onishi, Yukiko; Asano, Michiko; Kim, Hyosung; Ekholm, Ella; Johnsson, Eva; Yajima, Toshitaka
Abstract: Introduction: Dapagliflozin treatment when added to insulin therapy in Japanese patients with type 2 diabetes remains to be evaluated. Materials and Methods: This was a multicenter, randomized, double‐blind, parallel‐group, placebo‐controlled study to evaluate efficacy (at 16 weeks) and long‐term safety (at 52 weeks) of dapagliflozin in addition to insulin therapy. The interim analysis was carried out at week 16 to assess the efficacy and safety profiles. The patients receiving insulin ( n = 182) were randomized to either dapagliflozin 5 mg or a placebo at a 2:1 ratio. The primary efficacy end‐point was the change in hemoglobin A1c (HbA1c) from baseline at week 16. Results: Patients in the dapagliflozin group showed an adjusted decrease in HbA1c of −0.55% from baseline, whereas the placebo showed a marginal increase of 0.05%. The placebo‐corrected mean change of HbA1c from baseline to week 16 in dapagliflozin was −0.60% ( P < 0.0001). In addition, the placebo‐corrected mean change of fasting plasma glucose and bodyweight from baseline to week 16 in the dapagliflozin group was −22.7 mg/dL ( P < 0.0001) and −1.21 kg ( P < 0.0001), respectively. The placebo‐corrected mean daily insulin dose in the dapagliflozin group was numerically decreased (treatment difference: −0.72 IU/day; P = 0.0743). No major episodes or discontinuations as a result of hypoglycemia were reported during the study period. Conclusions: Dapagliflozin used as add‐on treatment to insulin therapy showed significantly greater reduction of HbA1c, fasting plasma glucose and bodyweight without severe hypoglycemia compared with the placebo at week 16. These results show the clinical benefit of prescribing dapagliflozin for Japanese patients with insufficient glycemic control even with insulin therapy.